Quantitative Analysis of Hand-finger Movement During Musical Expression in Early Childhood: Focusing on the Movement of the First Metacarpal Bone - Sano, Mina (Advances in Social Sciences Research Journal, 2025)
In this study, finger movement in early childhood was quantitatively analyzed to clarify their characteristics in musical expression. The Meta gloves system, which captures finger movements in detail, was connected to the MVN system used for movement analysis, and 3-year-old, 4-year-old, and 5-year-old children in the three child facilities participated in the movement analysis of musical expression (n=86). A three-way non-repeated analysis of variance was conducted on the calculated data for 19 types of finger movements, and several characteristics were found in the metacarpal bone of the first finger. A three-way non-repeated ANOVA for the total moving distance, the moving average velocity, the moving average acceleration and the moving smoothness regarding the first metacarpal bone verified a contrast between the moving average acceleration and the moving smoothness. Regarding the moving average moving acceleration, in all of participant facilities, the data for bright melodies were faster than the dark melodies, and it was observed in a tendency for the participant children to show larger pretend movement of imagination in response to the bright melodies, and a tendency was apparent for the participant children to show larger active movement in response to the bright melodies. This tendency was particularly clear in the participant children in Y facility. It was also found that finger movements were more pronounced for brighter tunes. The moving smoothness was observed in not very fast but a steady rhythm, but it was found that the moving smoothness was significantly larger for the dark melody than the bright melody.